ANALISIS PENGARUH CITRA RESTORAN DAN LOKASI TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Kusumaningtyas, Dhevi Dadi; Suddin, Alwi; Sriwidodo, Untung (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
The purpose of this study was to analyze the significance of the effect restaurant image and location on customer satisfaction, analyze the significance effect of restaurant image, location and satisfaction on consumer loyalty and analyze the significance effect of restaurant image and location on customer loyalty with satisfaction as intervening variables. This type of research is survey. The population of this research is consumer Go Martabak Kafe in Solo with a sample of 97 respondents with purposive sampling technique. Source of data used primary data and secondary data. The method of data collection used a questionnaire and literature. Data analysis techniques used path analysis. The results showed that the restaurant image has a significant effect on consumer satisfaction. Location has a significant effect on consumer satisfaction. The restaurant image has a significant effect on loyalty consumer. Location has a significant effect on the customer loyalty. Consumer satisfaction has a significant effect on customer loyalty. Consumer satisfaction has mediates the effect of restaurant image on customer loyalty. Consumer satisfaction has mediates the effect of location on customer loyalty.